Cost effectiveness of concurrent chemoradiation in comparison with radiation alone in locally advanced cervical cancer - Sumonmal Manusirivithaya (2018)
Introduction: Concurrent chemoradiation has been advocated to be more effective than radiation alone in the treatment of cervical cancer. However, it certainly has more side effects. Hence, it is worthwhile to investigate the cost-effectiveness (CE) of concurrent chemoradiation in comparison with radiation alone in locally advanced cervical cancer. Material and Method: The treatment of cervical cancer was modeled using the decision tree where the treatment option would be either concurrent chemoradiation or radiation alone. Patients receiving each treatment had different risks of tumor recurrence. Costs in this analysis were separated into four major categories: costs for treatment of cervical cancer, costs for treatment of major side effects, costs for follow up cancer patients, and costs for diagnosis including supportive care of recurrent cervical cancer. Charges were used for the costs of chemotherapy, radiotherapy, drugs, and accessories. Unit cost was used for the costs of laboratory investigations, in-patient and out-patient services. Costs incurred after the first year were discounted at an annual rate of 5%. The benefit was measured as months of life survived. The present study evaluated the patients to 5 years after complete treatment. Results: The CE ratio in the concurrent chemoradiation group was 2,855 and 1,835 Baht/month survived if the chemotherapy was given as in-patient and out-patient respectively. The CE ratio in the radiation group equaled 2,366 Baht/month survived. For the sensitivity analysis, in the situation that chemoradiation was not much better than radiation alone in terms that the recurrent rate from chemoradiation group was not more than 20% lower than the radiation group, radiation therapy alone would be more cost effective even if chemotherapy was given as an out-patient basis. Conclusion: Radiation alone was more cost effective than chemoradiation in the treatment of cervical cancer. Nevertheless, if chemotherapy was administered on an out-patient basis, chemoradiation will be more cost effective only if the recurrent rate from the chemoradiation group was more than 20% lower than the radiation group.